Attachment style and emotional eating in bariatric surgery candidates: The mediating role of difficulties in emotion regulation. (August 2015) - Taube-Schiff, Marlene; Van Exan, Jessica; Tanaka, Rika; Wnuk, Susan; Hawa, Raed; Sockalingam, Sanjeev
Abstract: Objective: Difficulties with emotion regulation is a hypothesized mechanism through which attachment insecurity may affect emotional eating. No studies have yet investigated this effect in the bariatric population. Because many obese individuals engage in emotional eating, difficulty regulating emotion may be an important underlying mechanism through which attachment insecurity is linked to emotional eating in bariatric surgery candidates. Methods: In this cross-sectional study, 1393 adult bariatric surgery candidates from the Toronto Western Hospital were recruited to complete the Emotional Eating Scale (EES), Patient Health Questionnaire-9 (PHQ9), Generalized Anxiety Disorder-7 (GAD7), Difficulties in Emotion Regulation Scale (DERS), Eating Disorder Examination Questionnaire (EDE-Q), and the Experiences for Close Relationships 16-item Scale (ECR-16) in order to explore the mediating role of emotion regulation on the relationship between attachment insecurity and emotional eating. Path analysis within a structural equation modeling framework examined direct and indirect effects of attachment insecurity on emotional eating. Results: The indices of this overall model indicated that the specified set of direct and indirect pathways and corresponding correlations were a good fit with the data (RMSEA < .06, CFI = 1.00; SRMR < .08). Moreover, tests of all of the possible indirect pathways between attachment style and emotional eating were significant. Discussion: Findings suggest that difficulties in emotion regulation may be an important mechanism to consider when examining the association between attachment insecurity and emotional eating in adult bariatric surgery candidates. Although causality cannot be concluded, these results shed light on the important role that emotion regulation may have in predicting problematic eating in bariatric patients. Highlights: Obese individuals have been found to engage in emotional eating We examined emotion regulation difficulties in a bariatric surgery patient population We found emotion regulation difficulties to be a potential mechanism through which attachment insecurity may affect emotional eating